PD-1 inhibitor therapy causes multisystem immune adverse reactions: a case report and literature review - Yin, Na; Liu, Xiangliang; Ye, Xiaojun; Song, Wei; Lu, Jin; Chen, Xiao (Frontiers in Oncology, 2022)
Immune checkpoint inhibitors（ICIs）, including cytotoxic T-lymphocyte antigen 4 (anti-CTLA-4), programmed cell death protein 1 and its ligand (PD-1/PD-L1) inhibitors, have been shown to have antitumor activity in various solid tumors. Their mechanism of action is to selectively restore and normalize the body’s immune reponses by disrupting the immunosuppressive signals mediated by PD-1, PD-L1 and CTLA-4 in the tumor microenvironment. With the increase in clinical applications of ICIs, reports of immune-related adverse events (irAEs) have also increased. This article reports a case of a lung cancer patient who developed multisystemic adverse effects after PD-1 inhibitor application: myocarditis, myositis and thrombocytopenia, and analyzes the role of Interleukin 6（IL-6）in the management of irAEs. Despite the patient's eventual discontinuation of antitumor therapy due to severe irAEs, a significant and durable therapeutic response was observed.